KERAGAMAN 13 AKSESI TANAMAN JERUK BESAR (Citrus maxima Merr.) DI KABUPATEN BIMA - Sumarjan Sumarjan; Nurrachaman Nurrachaman; Istiana Istiana (Bioscientist : Jurnal Ilmiah Biologi, 2019)
Inventory and characterization of large citrus fruit populations are needed to determine identity and selection to facilitate the dissemination of information and communication in breeding programs. The purpose of this study was to determine the diversity of accessions of the Citrus maxima Merr plant. (Big Orange) found in Bima Regency. The research method used in this research is descriptive exploration method. Morphological diversity is based on the results of morphological observations that are analyzed using the MINITAB 13 program then grouping with complete linkage based on distance taxa (Squared Euclidean Distence). The results showed that the number of large Jeruk cultivars found in Bima Regency were 13 cultivars (A, B, C, D, E, F, G, H, I, J, K, L, and M) grouped into 2 main groups and 4 sub groups. Based on the 13 accessions observed, accessions F and J had the greatest level of equality with emotive characteristics more than 75%.